2011
DOI: 10.4238/vol10-2gmr1127
|View full text |Cite
|
Sign up to set email alerts
|

Association of KCNJ11 with impaired glucose regulation in essential hypertension

Abstract: ABSTRACT. KCNJ11 is one of the candidate genes for type 2 diabetes, confirmed by genome wide association study, but there are little data on the relationship between KCNJ11 and impaired glucose regulation in essential hypertension patients. To identify the effect of E23K and I337V in the KCNJ11 gene on susceptibility to impaired glucose regulation, we conducted a case control study in 1125 essential hypertension patients with or without impaired glucose regulation among a Han Chinese population. We also evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…A total of 49 eligible reports investigated the association between SNPs and the gAUC after an OGTT in 39 different cohorts, i.e., Quebec Family Study [ 12 , 13 , 14 , 15 , 16 , 17 ], Amish Family Diabetes Study [ 18 , 19 ], Ely Study [ 20 ], Tübingen Family Study (TÜF) [ 21 ], European Atherosclerosis Research Study (EARS II) [ 22 , 23 ], Sapphire Study [ 24 ], Metabolic Intervention Cohort Kiel (MICK) [ 25 , 26 ], European Network on Functional Genomics of Type 2 Diabetes (EUGENE2) [ 27 , 28 ], Metabolic Syndrome in Men (METSIM) [ 28 ], Metabolic Syndrome Berlin Potsdam Study (MESYBEPO) [ 29 ], Lifestyle Intervention in a General Population for Prevention of Ischaemic Heart Disease (Inter99) [ 30 , 31 ], Berlin Ernährung Geschwister Study (BErG-Study) [ 32 ], and further 27 cohorts without a specific study name [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 49 eligible reports investigated the association between SNPs and the gAUC after an OGTT in 39 different cohorts, i.e., Quebec Family Study [ 12 , 13 , 14 , 15 , 16 , 17 ], Amish Family Diabetes Study [ 18 , 19 ], Ely Study [ 20 ], Tübingen Family Study (TÜF) [ 21 ], European Atherosclerosis Research Study (EARS II) [ 22 , 23 ], Sapphire Study [ 24 ], Metabolic Intervention Cohort Kiel (MICK) [ 25 , 26 ], European Network on Functional Genomics of Type 2 Diabetes (EUGENE2) [ 27 , 28 ], Metabolic Syndrome in Men (METSIM) [ 28 ], Metabolic Syndrome Berlin Potsdam Study (MESYBEPO) [ 29 ], Lifestyle Intervention in a General Population for Prevention of Ischaemic Heart Disease (Inter99) [ 30 , 31 ], Berlin Ernährung Geschwister Study (BErG-Study) [ 32 ], and further 27 cohorts without a specific study name [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ...…”
Section: Resultsmentioning
confidence: 99%
“…In one study, a glucose amount of either 50 or 75 g was used without any justification [ 42 ]. While in most of the reports, the duration of the OGTT lasted 120 min [ 20 , 21 , 22 , 23 , 24 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 36 , 37 , 38 , 39 , 41 , 43 , 44 , 45 , 47 , 48 , 50 , 52 , 53 , 54 , 56 , 57 , 58 , 59 , 60 ] or 180 min [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 35 , 40 , 42 , 49 , 51 , 55 ], in either two reports the OGTT was performed over 240 min [ 25 , 26 ] or 300 min [ 34 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present case-control study, the association of KCNJ11 (rs5219 and rs2285676) and KCNMB1 (rs11739136) gene polymorphisms with EH was explored in a Kazak population. Previous studies have demonstrated that there is an association between different KCNJ11 SNPs and EH and diabetes in different populations ( 33 35 ). However, to the best of our knowledge, there are no studies that have been performed with these SNPs in the Kazak population.…”
Section: Discussionmentioning
confidence: 99%